IMPLEMENTASI MANAJEMEN STRATEGIK PENGELOLAAN ZAKAT PRODUKTIF DI LEMBAGA KEUANGAN PUBLIK ISLAM (STUDI PADA DOMPET DHUAFA YOGYAKARTA) - Fajar Fandi Atmaja; Rahmani Timorita Yulianti; Martini Dwi Pusparini; Nurul Wulandari Putri; Naili Jannati (Jurnal Dinamika Ekonomi & Bisnis, 2017)
One type of philanthropy in Islam is zakah. In general, the distribution of zakah can assist in alleviating poverty problem. Public financial institutions such as BAZ and LAZ as a non-profit financial institutions have an important role in the management of zakat funds. Along with the development of today's management, now many LAZ using differentpatterns in the zakat funds management, including strategic management. This study aims to determine the implementation of the strategic management of Islamic public financial institutions and strategies applied in the management of productive zakah.Thi study belongs to field research with descriptive-qualitative approach. The subject of the study is Dompet Dhuafa Yogyakarta. Data collecting is done by interview and documentation. This method is used to deduce the results of the study on the implementation of the strategic management of productive zakah fund management in Dompet Dhuafa Yogyakarta.The result of the research shows that Dompet Dhuafa Yogyakarta has implemented strategic management in productive zakah management. From the analysis of company profiles and environmental analysis, it is known that strength, weakness, opportunities, and threats overall  illustrate that Dompet Dhuafa Yogyakarta are in a strong position because of the level of opportunity dominance is more than the threat it faces. It also indicates that the Dompet Dhuafa Yogyakarta can continue to grow. Grand strategies applied by Dompet Dhuafa Yogyakarta include: expanding programs and networks in fundraising and utilization, upgrading excellent customer service, building strategic alliances for resource mobilization and advocacy, building ICT systems, internal controls, transparency and accountability, and building a human resource management system.